Mineralogy of Alluvial Soils Developed in Narmada River Basin in West Coast of Gujarat - R.P. Sharma; B.P. Bhaskar; R.K. Naitam; B. Dash; G. Tiwari; A. Jangir (Journal of the Indian Society of Soil Science, 2023)
Clay minerals have played a significant role for the plant nutrient management for crop production. Soils of recent and old alluvial plains deposited by Narmada river in Jhagadia block were investigated for their mineralogical makeup. The soils on recent alluvial plains (P1) (Fluventic Haplustepts) are very deep, moderately well drained, very dark grayish brown to very dark brown, silt loam to silt clay loam on level to nearly level slope with clay loam surface and slight erosion. The soils of old alluvial plain (P2) (Vertic Haplustepts) are similar to recent alluvial plain with clayey texture and moderate erosion. The pedons were sampled at one km (recent alluvial plain) and at two km (old alluvial plain) distance from Narmada river stream. The soils of recent alluvial plain are slightly alkaline (pH 7.5-8.5), slightly calcareous (<5% CaCO3) with moderate cation exchange capacity (CEC) and high in base saturation (>90%). The soils of old alluvial plain have high CEC and CaCO3 in sub-surface horizons. This paper presents a detailed study on clay minerals in surface and sub-surface sediments deposited by the Narmada river drainage basin. Clay content was ranged from 30-50% in recent alluvia and 50-60% in old alluvia. The soils of recent alluvia were high in silt fraction (40-47%) which plays an active role in potassium nutrition. The smectite content was significantly higher (weighted mean 64.9%) in old alluvial plain compared with recent plain (weighted mean 37.8%). A reverse pattern of mica distribution was observed in clay fraction of both the plains. The distribution of quartz and K/Na feldspars showed similar trends in sand fraction but wide variability was observed in the case of hydralsite, kenyaite, and boehmite content with depth. The mineralogical study indicated that the clay mineral assemblage of both sites varied in smectites and mica, which imparts heterogeneity to soil properties.